2018
DOI: 10.3390/molecules23081900
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Binding Interaction between Bovine Lactoferrin and Tetracycline Hydrochloride: Multi-Spectroscopic Analyses and Molecular Modeling

Abstract: In this paper, the interaction between bovine lactoferrin (bLf) and tetracycline hydrochloride (TCH) was researched by microscale thermophoresis (MST), multi-spectroscopic methods, and molecular docking techniques. Normal fluorescence results showed that TCH effectively quenched the intrinsic fluorescence of bLf via static quenching. Moreover, MST confirmed that the combination force between bLf and TCH was very strong. Thermodynamic parameters and molecular docking further revealed that electrostatic forces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…It was similar to some other published papers that found no peaks in the UV‐Vis spectrum of Fe 3 O 4 NPs (Vollath, 2013 ). Meanwhile, LF showed a peak in the UV region at the wavelength of 280 nm (Figure 2b , curve b), in agreement with other reported studies (Sun et al., 2018 ). The LF‐ bis ‐MPA‐MNPs showed a peak at the wavelength of 275 nm (Figure 2b , curve c), which indicated that LF was successfully coated on Fe 3 O 4 NPs.…”
Section: Resultssupporting
confidence: 92%
“…It was similar to some other published papers that found no peaks in the UV‐Vis spectrum of Fe 3 O 4 NPs (Vollath, 2013 ). Meanwhile, LF showed a peak in the UV region at the wavelength of 280 nm (Figure 2b , curve b), in agreement with other reported studies (Sun et al., 2018 ). The LF‐ bis ‐MPA‐MNPs showed a peak at the wavelength of 275 nm (Figure 2b , curve c), which indicated that LF was successfully coated on Fe 3 O 4 NPs.…”
Section: Resultssupporting
confidence: 92%
“…Alternatively, bLf could be detected by its intrinsic fluorescence. 30,31 Therefore, we optimized the fluorescent condition with excitation and emission wavelengths of 280 and 344 nm, respectively. As a result, the fluorescent detection showed a much higher sensitivity than UV detection (Figure S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The CD spectra showed a decrease in negative band intensity as a result of the increasing degree of derivatization with TCH. They explained the reduction by breaking of hydrogen bonds due to TCH conjugation of lactoferrin and hypothesized that the altered secondary structure might also affect physiological functions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the determination of freely available amino groups plays a crucial role with regard to the properties and functionality of proteins [ 1 , 152 ]. Knowledge of the influence of chemical modifications on protein structure and surface hydrophobicity allows conclusions to be drawn about solubility, aggregation, and physical stability [ 52 , 153 ], which are particularly important with regard to food processing and food safety [ 1 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation